GENERATIVE CAPABILITIES OF ARTIFICIAL INTELLIGENCE. REVIEW OF GENERATIVE TOOLS IN EDUCATION ON THE EXAMPLE OF THE WEBSITE KURAPLAN.COM - Khasanov Zafar Shavkat oglu (Uzbekistan Open Conference, 2025)
The article addresses current issues related to the integration of artificial intelligence (AI) technologies into the educational process. It analyzes the advantages and risks associated with the use of AI and presents the results of a study on teachers’ and students’ attitudes toward these technologies. Particular attention is paid to the practical application of AI for automating the creation of educational materials. The platform KuraPlan.com is examined as a case study—an online service that employs generative AI to design syllabi and calendar-thematic plans. It is demonstrated that integrating such tools helps reduce the administrative workload of teachers, personalize learning, and improve the overall efficiency of the educational process.
Keywords: Artificial intelligence; digital didactics; generative AI; educational automation; syllabus; calendar-thematic planning; KuraPlan.com; instructional design